Problem Solving Over Regulasi di Indonesia - Muhammad Khaidir Kahfi Natsir (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
This study examines the phenomenon of regulatory obesity in Indonesia and its implications for legal stability and economic development. As a state based on the rule of law, Indonesia faces challenges arising from the excessive number of regulations and frequent regulatory changes influenced by political interests. This research aims to identify the factors contributing to overlapping regulations and regulatory conflicts and to analyze their impact on governance and economic activities. A qualitative approach was employed using secondary data from official documents, legislation, and relevant literature. The findings show that between 2014 and 2019, Indonesia issued 10,180 regulations, including laws, government regulations, presidential regulations, and ministerial regulations. The large number of regulations has created policy disharmony, particularly across interconnected sectors, resulting in legal uncertainty, administrative inefficiency, and obstacles to economic growth. Furthermore, excessive regulation generates confusion among the public and business actors while reducing the effectiveness of policy implementation. This study recommends the adoption of the Omnibus Law approach as a strategic solution to simplify regulations, improve legal coherence, and enhance regulatory effectiveness. Regulatory reform is therefore essential to create a fair, transparent, and responsive legal environment that supports sustainable development and effective governance in Indonesia.